2015
DOI: 10.14348/molcells.2015.2327
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of Long Non-Coding RNA HOTAIR Promotes Tumor Growth and Metastasis in Human Osteosarcoma

et al.

Abstract: Human osteosarcoma usually presented a high tendency to metastatic spread and caused poor outcomes, however, the underlying mechanism was still largely unknown. In the present study, using a series of in vitro experiments and an animal model, we investigated the roles of HOX antisense intergenic RNA (HOTAIR) during the proliferation and invasion of osteosarcoma. According with our results, HOTAIR was commonly overexpressed in osteosarcoma, which significantly correlated with advanced tumor stage, highly histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 54 publications
2
59
0
Order By: Relevance
“…Furthermore, Hotair seemed to be required for repression of HoxD genes and several imprinted loci such as Dlk1-Meg3 and Igf2-H19 , without affecting imprinting choice (61). In analogy to our study, it has been shown that knockdown of HOTAIR impairs proliferation (62). The results of our study support the notion that HOTAIR is also important to modulate proliferation and differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, Hotair seemed to be required for repression of HoxD genes and several imprinted loci such as Dlk1-Meg3 and Igf2-H19 , without affecting imprinting choice (61). In analogy to our study, it has been shown that knockdown of HOTAIR impairs proliferation (62). The results of our study support the notion that HOTAIR is also important to modulate proliferation and differentiation of MSCs.…”
Section: Discussionsupporting
confidence: 82%
“…LncRNAs have been employed as biomarkers and therapeutic targets in various skeletal diseases including osteoarthritis and osteoporosis, as well as in cancers related to the skeletal system [23], among which the lncRNA DANCR has been observed to act as a regulatory element in patients suffering from osteoporosis [9]. Elevated expression of the lncRNA MyoD has been detected in skeletal muscle cells, and elevated lncRNA HOTAIR expression has been observed in osteosarcoma tissues [24,25]. DLL3 is a spondylocostal dysplasia/pudgy gene whose mutation may lead to axial skeletal defects and spondylocostal dysostosis [26][27][28].…”
Section: Figure 14mentioning
confidence: 99%
“…7 The important epigenetic modification modes of DNA methylation and histone methylation are known to directly regulate the expression of various tumor-related genes. 8, 9 Aberrant DNA methylation and histone methylation, mediated by HOTAIR, have been found in many types of tumors.…”
mentioning
confidence: 99%